2019
DOI: 10.1111/pedi.12836
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes camp still matters: Relationships with diabetes‐specific distress, strengths, and self‐care skills

Abstract: Objective Prior studies suggest diabetes camps improve psychosocial well‐being in youth with type 1 diabetes but these studies suffer from variable levels of rigor. The present study assessed associations between camp participation and diabetes distress, perceived independence in diabetes self‐care, and diabetes strengths in a large sample of children, adolescents, and their parents across 44 camps in the United States. Analyses compared viewpoints of study participants, identified moderators of change, and as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…59 Going to diabetes camp helped some of the emerging adults in this study with this integration as well and helped to decrease the developmental challenges they faced, which is in line with what others have found. 60,61 As for all emerging adults with T1DM, [6][7][8][9][10][11][12]55 the desire to appear normal in front of peers and colleagues vs wanting to be in control of their diabetes was a big challenge for our study participants. It was an especially big issue for the younger subset of study participants, both males and females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59 Going to diabetes camp helped some of the emerging adults in this study with this integration as well and helped to decrease the developmental challenges they faced, which is in line with what others have found. 60,61 As for all emerging adults with T1DM, [6][7][8][9][10][11][12]55 the desire to appear normal in front of peers and colleagues vs wanting to be in control of their diabetes was a big challenge for our study participants. It was an especially big issue for the younger subset of study participants, both males and females.…”
Section: Discussionmentioning
confidence: 99%
“…59 Going to diabetes camp helped some of the emerging adults in this study with this integration as well and helped to decrease the developmental challenges they faced, which is in line with what others have found. 60,61…”
Section: Discussionmentioning
confidence: 99%
“…In our study, use of the G6's remote monitoring feature was precluded; however, camps that have implemented remote monitoring of CGM data observed significant reductions in hypoglycaemia, particularly overnight. 14,15 Our study contributes to a body of evidence 4,5 indicating that diabetes camps reduce diabetes-related distress, promote shortterm improvements in glycaemic control and enhance quality of life.…”
Section: Discussionmentioning
confidence: 81%
“…continuous glucose monitoring, diabetes camp, glycaemic control, quality of life of life, [2][3][4] and haemoglobin A1c (HbA1c) levels. 5 However, few studies have examined whether glycaemic control at home prior to camp is different than that during camp.…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not formally meta‐analyze nutritional knowledge, the two studies which provided data both showed significant improvements after camp 13,49 . Likewise, the relatively recent concept of diabetes distress (an emotional state where a person living with diabetes experiences concerns about disease management, support, emotional burden, and access to care 54 ) was noted to be reduced after summer camp in two recent large US reports from the same research group 48,55 …”
Section: Discussionmentioning
confidence: 93%